Strategic analysis and knowledge support systems for rural development strategies in Sub-Saharan Africa - Johnson, Michael E.; Resnick, Danielle; Bolwig, Simon; Chamberlin, Jordan; You, Liangzhi; Wood, Stanley; Hazell, Peter B. R. (International Food Policy Research Institute, 2004)
While greater growth in agriculture and the broader rural sector is crucial for ameliorating Africa's high levels of poverty and malnutrition, developing strategies to achieve these objectives is hindered by a number of factors, including the broad array of interventions needed, the lack of accurate data, and dearth of trained local policy analysts. As such, this paper proposes a Strategic Analysis Knowledge Support System (SAKSS) in which data, tools, and knowledge are compiled, analyzed, and disseminated for the purposes of identifying a set of priority investment and policy options to promote agricultural growth and rural development. These analyses can in turn help inform the broader process of designing, implementing, and monitoring and evaluating a country's rural development strategy. In order to be an influential and sustainable part of this process and become a genuine "knowledge system," SAKSS will need to be established with an awareness of each country s development priorities and unique political, social, and economic context. By institutionalizing SAKSS through a network structure that includes government ministries, research institutions, universities, regional organizations, non-governmental organizations, and donors, SAKSS can become not only more relevant and legitimate for its intended end-users but also help strengthen local analytical capacity to inform the policy debate on future development strategies and outcomes."-- Authors' Abstract